Efficient Homocoupling of Aryl- and Alkenylboronic Acids in the Presence of Low Loadings of [{Pd(μ–OH)Cl(IPr)}2] - Ostrowska, Sylwia; Rogalski, Szymon; Lorkowski, Jan; Walkowiak, Jędrzej; Pietraszuk, Cezary (Synlett, 2018)
NHC–palladium(II) complex [{Pd(μ–OH)Cl(IPr)}2] (IPr = bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) catalyzes the oxidative coupling of a broad spectrum of aryl- and alkenylboronic acids at loadings down to 5 ppm. At the concentration of 0.05 mol% the catalyst permits an efficient reaction under base-free conditions.
Keywords: homogeneous catalysis; palladium; NHC complexes; homocoupling; boronic acids